Dynamic mechanical properties and energy dissipation analysis of frozen sandstone with initial damage - Xie, Qihang; Chen, Yanlong; Lyu, Haoyan; Gu, Jun; Chen, Yuanguang; Cui, Huidong; Wu, Peng (Frontiers in Earth Science, 2023)
Damaged rock masses on the slopes of open pit coal mines are prone to geological disasters such as landslides under low temperatures and dynamic loads such as blasting impacts. Based on the Low Temperature Split Hopkinson Pressure Bar (LT-SHPB) system, dynamic compressive tests were done on sandstone specimens, which were damaged by uniaxial loading and unloading test. Dynamic stress–strain curves and dynamic mechanical properties of frozen sandstone with initial damage were analyzed as well as the energy dissipation characteristics. The results indicate that both compressive state and plastic deformation state of the dynamic stress-strain curves increase with the increase of the damage value. Dynamic peak stress and dynamic elastic modulus exhibit an evident damage weakening effect while the dynamic peak strain, in contrast, exhibits a damage enhancement effect. In addition, all three dynamic mechanical properties of the damaged frozen sandstone exhibit an impact effect. The dissipation energy ratio and reflection energy ratio of frozen sandstone increase with the increase of initial damage value while the transmission energy ratio decreases. With the increase of initial damage value and strain rate, the energy utilization rate during the sandstone failure process increases, resulting in more small fragments and powders.